2010
DOI: 10.1289/ehp.0901207
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Vascular Effects from Complex and Individual Air Pollutants Indicates a Role for Monoxide Gases and Volatile Hydrocarbons

Abstract: BackgroundEmerging evidence suggests that the systemic vasculature may be a target of inhaled pollutants of vehicular origin. We have identified several murine markers of vascular toxicity that appear sensitive to inhalation exposures to combustion emissions.ObjectiveWe sought to examine the relative impact of various pollutant atmospheres and specific individual components on these markers of altered vascular transcription and lipid peroxidation.MethodsApolipoprotein E knockout (ApoE−/−) mice were exposed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 35 publications
(60 reference statements)
3
52
0
Order By: Relevance
“…The main results of the study by CAMPEN et al [87] indicate that gasoline and, to a lesser extent, diesel exposure induced MMP-9 mRNA expression and activity in the aorta. Interestingly, whereas gasoline exposure also induced an increased gelatinase activity, such an effect was absent after exposure to diesel combustion.…”
Section: Induction Of Mmps By Complex Mixtures (Gases and Particles)mentioning
confidence: 92%
See 2 more Smart Citations
“…The main results of the study by CAMPEN et al [87] indicate that gasoline and, to a lesser extent, diesel exposure induced MMP-9 mRNA expression and activity in the aorta. Interestingly, whereas gasoline exposure also induced an increased gelatinase activity, such an effect was absent after exposure to diesel combustion.…”
Section: Induction Of Mmps By Complex Mixtures (Gases and Particles)mentioning
confidence: 92%
“…In order to better understand the role of the different components of gasoline exhaust on MMP induction and activation, the same group of investigators analysed the comparative effects of various gases representative of gasoline exhaust on vascular toxicity and MMP-9 expression and activity [87]. Exposure atmospheres included gasoline and diesel engine exhaust, hardwood smoke, a simulated ''downwind'' coal combustion atmosphere (SDCCA), biogenically derived secondary organic aerosols (SOAs), and individual combustion source gases (nitric oxide (NO), NO 2 and CO).…”
Section: Induction Of Mmps By Complex Mixtures (Gases and Particles)mentioning
confidence: 99%
See 1 more Smart Citation
“…The SPHERES program was developed to enable the development of irradiation chamber technology that is coupled to inhalation exposure systems and to subsequently carry out toxicological experiments to comprehensively evaluate the potential toxicity of SOA. The results of the SPHERES studies on α-pinene have been reported Campen et al, 2010). This manuscript reports on the design and characterization of the SPHERES inhalation system along with initial findings assessing the cardiopulmonary response in rodents exposed to SOA derived from the oxidation of a single anthropogenic hydrocarbon (i.e.…”
Section: Research Articlementioning
confidence: 99%
“…Studies beyond laboratory exposure to single pollutants are relatively rare, but there are useful examples (Ayala et al, 2012;Campen et al, 2010;Ljubimova et al, 2013;Mauderly et al, 2010;Seilkop et al, 2012). The linkage between air chemistry and exposure could be exploited with study designs that take advantage of advanced aerosol generation and analytical methods to provide aged mixtures to in vitro or in vivo procedures.…”
Section: Comments By George M Hidymentioning
confidence: 99%